Earth-tubes for Building Heating and Cooling in Drylands - George, Camille (Annals of Arid Zone, 2016)
Building heating and cooling strategies for dryland communities should consider the needs of modern cities as well as traditional agriculturalists. Successful heating and cooling approaches must therefore be economically viable in both urban and rural settings as well as environmentally safe and sustainable. ()ne low energy alternative for conditioning building space is to pass ambient air through t:arth tubes, which are long buried tubes also known as earth to air heat exchangers, through the relatively stable environment of the subsurface before being delivered and/or circulated through living space. The difference between the temperature of the outside air and that of the ground results in a cooling or heating effect on the transported air depending on the time of the day and/or year. In the past few decades the use of earth tubes has evolved from preliminary numerical, analytical and experimental investigations to commercial adoption. This paper presents an overview of the fundamentals of earth tube design and installation. Several published dryland applications are reviewed and the potential to cool or to heat buildings in a hot and in a cold dry region are discussed. This low-tech low-energy technology can be .a viable strategy for the improvement of health and life in dry and arid climates in remote rural settings, as well as a technology that can significantly decrease the energy demand to condition space in rapidly growing urban centers. Key words: Earth tubes, earth-to-air heat exchan!!ers, ground air heat exchange, sustainable buildings.